Role of ultrasound and inflammatory factors in the management of pediatric hip joint effusion - Seyed Ali Alamdaran; Mohadeseh Taheri-nezhad; Ahmad Nouri; Farzaneh Khoroushi; Mohammad Hasan Aalami; Abdoreza Malek; Arezou Mohtasham; Mohamadreza Alizadeh (BMC, 2023)
Abstract Background Septic arthritis is an important differential diagnosis of hip joint pain. Joint aspiration analysis is a necessary diagnostic measure for septic arthritis. In order to reduce the need for joint aspiration, we compared the combination of ultrasound findings and laboratory findings to separate septic arthritis from reactive arthritis. Methods Children aged < 14 years who were referred to Akbar pediatric hospital in 2020-2022 with hip pain or limping were included in this longitudinal study. Participants underwent ultrasound examinations of the hip and blood samples were obtained from them. After confirming an effusion, dependent on patient status and clinical diagnosis, one of the following approaches was recommended; the close follow-up, or the ultrasound-guided aspiration of the hip joint effusion, and or arthrotomy. The various ultrasound and laboratory were documented. Data were analyzed and P < 0.001 being considered statistically significant. Results Overall, 115 patients with a mean age of 3.43 ± 5.76 years, 46 of whom were girls, were studied. The final diagnosis in 23 cases (20.0%) was septic arthritis and 92 (80.0%) had reactive arthritis. C-reactive protein (CRP) and The erythrocyte sedimentation rate (ESR) unlike aspirate volume, effusion volume measured on ultrasound, capsule thickness, total thickness, and recorded capsule-to-effusion ratio were significantly higher in patients with septic arthritis (P < 0.001). There was a significant agreement between the volume of measured fluid in the anterior recess and the volume of aspirated fluid (2.5 times, P < 0.001). Septic arthritis was not observed in any of the patients with effusion volume in anterior recess less than 0.5 cc and ESR less than 40 mm/hr or CRP less than 15 mg/L. Conclusion Since septic arthritis was not observed in any of the patients with effusion volume < 0.5 cc and normal inflammatory factors (ESR or CRP), conservative management and close follow-up can be recommended in these patients instead of joint fluid aspiration.